Assessing the impact of ChatGPT in education: perspectives from Vietnamese educators - Nguyen Thi Thu Thuy; Nguyen Thi Kim Lien; Phan Thi Van; Hoang Phuong Lam; Nguyen Le Thanh Truc (Institute of Advanced Engineering and Science, 2026)
ChatGPT is an AI-driven conversational model offering significant benefits for personalized learning, such as adaptability to individual learning styles and increased engagement. While prior research has largely explored student use, limited attention has been given to educators’ perspectives particularly in Vietnam, where access to ChatGPT remains inconsistent. This study examines how perceived information quality (IQ), system quality (SQ), and service quality (SRQ) influence Vietnamese educators’ satisfaction (SF) and intention to use (IU) ChatGPT for academic purposes. Data were gathered through an online survey of 96 educators from five public universities in southern Vietnam and analyzed using partial least squares structural equation modeling (PLS-SEM). Results show that all three quality dimensions significantly affect user SF, but only SQ directly impacts the IU. SF mediates the effects of information and SRQ on usage intentions, emphasizing the importance of user experience in fostering adoption. Policy recommendations include enhancing equitable access to AI tools, promoting AI literacy among educators, and conducting ongoing evaluations to support sustainable implementation. The study highlights how spatial and contextual factors shape AI adoption in education, offering practical insights for integrating ChatGPT and similar tools, especially in under-resourced or geographically remote educational settings.